Tailoring electrocaloric properties of Ba1-xSrxSnyTi1-yO3 ceramics by compositional modification. Issue 1 (January 2022) - Molin, C.; Richter, T.; Gebhardt, S.E.
Abstract: This paper presents compositional modifications on lead-free material system based on barium titanate to optimize its electrocaloric (EC) properties. By addition of strontium and tin we prepared solid solutions of Ba1-x Srx Sny Ti1-y O3 (BSSnT-100∙x-100∙y) which allow for shifting of maximum EC effect to room temperature as well as broadening the temperature range of high EC temperature changes Δ T E C . Bulk ceramic samples of BSSnT were prepared by solid-state reaction route and the influence of Sn:Sr ratio on dielectric and ferroelectric properties was investigated. The EC temperature change was measured directly using resistance welded thermocouple wires. Most promising results could be achieved for BSSnT-18−6.5, which showed a maximum Δ T E C of 0.49 K around 30 °C with Δ T E C > 0.3 K in the temperature range from 10 °C to 50 °C under a comparatively low electric field change of 2 V μm −1 .